2014
DOI: 10.1016/j.seizure.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiovascular risk factors and troponin elevation after generalized tonic-clonic seizures

Abstract: Elevated troponin levels can occur after a GTC seizure. Patients at risk are the elderly and those with cardiovascular risk factors. Our results suggest that elevation of troponin levels after a GTC seizure reflects a minor ischemic cardiac injury related to the demand ischemia during the sympathetic overactivity that accompanies a GTC seizure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…Elevations of cTNI may hint to the cardiac stress that epilepsy patients are exposed to during GTCS. Twelve percent of our patients displayed cTNI elevations, which is in line with most previous ER studies [ 17 20 ] reporting cTNI elevations in 6.5–28.6% of their patients. However, Woodruf [ 21 ], Alehan [ 22 ] Eskandarian [ 23 ] and Hajsadeghi [ 24 ] found no cTNI elevations in their patient groups, but these studies excluded patients with preexisting cardiovascular conditions or examined children and adolescents only.…”
Section: Discussionsupporting
confidence: 92%
“…Elevations of cTNI may hint to the cardiac stress that epilepsy patients are exposed to during GTCS. Twelve percent of our patients displayed cTNI elevations, which is in line with most previous ER studies [ 17 20 ] reporting cTNI elevations in 6.5–28.6% of their patients. However, Woodruf [ 21 ], Alehan [ 22 ] Eskandarian [ 23 ] and Hajsadeghi [ 24 ] found no cTNI elevations in their patient groups, but these studies excluded patients with preexisting cardiovascular conditions or examined children and adolescents only.…”
Section: Discussionsupporting
confidence: 92%
“…Value of troponins ranged between 5.5 ng/mL and 6.3 ng/mL, in contrast to our case in which troponins were very highly elevated from 12.57 to 49.64 ng/mL [6]. A study of 14 patients with cardiovascular disease risk factors also demonstrated some correlation between seizures and raised troponins levels [7]. The pathophysiology remains obscure but there might be other underlying causes of raised troponin which were not ruled out.…”
Section: Discussioncontrasting
confidence: 91%
“…There is limited research that investigates the link between seizures and troponin rise and therefore the exact pathophysiology is controversial (Fawaz et al, 2014). However, considering the autonomic innervation of the heart, periseizure cardiac changes are not surprising according to Jansen and Lagae (2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that the hyperadrenergic state during convulsions leads to a perfusion/demand mismatch resulting in myocardial injury and rise in troponins (Gaspard, 2019). Although troponins are considered to be specific to cardiac injury, troponin elevation has been reported in non-acute coronary syndrome events such as myocarditis, pericarditis, sepsis and rhabdomyolysis (Fawaz et al, 2014). As our patient did not have any of the above conditions, the possibility of a minor ischaemic myocardial injury due to the perfusion/demand mismatch seems more likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation